1982
DOI: 10.1002/qua.560220220
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of triatomic interhalogens

Abstract: Although a number of trihalide ions have long been experimentally characterized [I], very little is known about the parent neutral radicals. Available experimental [ 11 and ab initio theoretical [2,3] Ungemach and Schaefer [2] support the experimental structure of ClF2, but no such theoretical study has yet been made to substantiate the observed structure of c13. The CND0/2 (spd) calculations of Vasini and Castro [9] on C I S and CI3 indicate that both the radicals possess a linear symmetric structure. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…[17][18][19][20][21][22][23] Emission spectra attributable to Cl 3 were observed by Kawasaki et al 14 and Wright et al 15 These data were in reasonable agreement with each other. An IR spectrum of Cl 3 in a Kr matrix was reported by Nelson and Pimentel.…”
Section: Introductionsupporting
confidence: 72%
“…[17][18][19][20][21][22][23] Emission spectra attributable to Cl 3 were observed by Kawasaki et al 14 and Wright et al 15 These data were in reasonable agreement with each other. An IR spectrum of Cl 3 in a Kr matrix was reported by Nelson and Pimentel.…”
Section: Introductionsupporting
confidence: 72%
“…Following this work, Wright et al suggested that a 370−420 nm emission band, observed when Cl 2 was photodissociated under relatively high-pressure conditions, might also originate from Cl 3 . In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio , and semiempirical methods. , …”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio 15,[24][25][26] and semiempirical methods. 9,[27][28][29][30][31][32] Recently, additional interest in the trihalogens has been generated by novel time-resolved studies of the Br + I 2 reaction. 1,[33][34][35][36] From the results on this system, it appears that trihalogens, accessed through photodissociation of HX-YZ complexes, may be especially suitable for real-time studies of reaction dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation